CHARACTERISTIC OF ACRYLIC ACID GRAFTED POLYETHYLENE FILM PREPARED BY GAMMA IRRADIATION METHOD - John Hendri; Irwan Ginting Suka; Wasinton Simanjuntak; Annisa Annisa; Gatot Gatot (Indonesian Journal of Chemistry, 2008)
In this study, high density polyethylene (PE) film (thickness 80 μm) was modified by grafting of acrylic acid (AA) onto the film using 15 kGy of g irradiation as initiator, applied at different exposure times. In addition to irradiation dose, other variables investigated are concentration of AA, the type of solvent, and polymerization time carried out at 60 oC. The success of the graft copolymerization processes was confirmed by analysing the grafted film using FTIR spectroscopy, which revealed the existence of absorption band at wave number of 1721 cm-1(assigned to C=O), and that at 3385 cm-1 (assigned to -OH), and the physical endurance of the sample was evaluated by carrying out tensile strength measurement. The percent of grafting was determined according to the gravimetric method. The results indicated that the highest percent of grafting was obtained by application of 2-hour irradiation time, with monomer concentration of 30 % in water as a solvent, grafting temperature of 60 oC. Activity of grafted was evaluated by measurement of the absorption capacity toward water and Cu2+ ion, and revealed the increase of the absorption capacity with increased percent of grafting.